Mediterranean diet in preeclampsia prevention: mechanisms of action and clinical evidence - Baroutis, Dimitris; Papadopoulos, Alexander; Giannakaki, Aikaterini-Gavriela; Katsianou, Eleni; Antsaklis, Panagiotis; Theodora, Marianna; Daskalakis, George; Kotsis, Thomas (Frontiers in Nutrition, 2025)
IntroductionPreeclampsia, affecting 2–5% of pregnancies globally, represents a significant challenge in maternal-fetal medicine with substantial morbidity and mortality. Anti-inflammatory dietary patterns, particularly the Mediterranean diet, may ameliorate preeclampsia risk through modulation of inflammatory mediators, oxidative stress, and vascular function. Current findings regarding diet and preeclampsia prevention exhibit considerable variability. We conducted a comprehensive review to evaluate the association between the Mediterranean diet and other anti-inflammatory dietary patterns with preeclampsia risk.MethodsWe performed a systematic literature search across multiple databases including PubMed/MEDLINE, Embase, Google Scholar, ScienceDirect, Scopus, and Web of Science from September 2024 to March 2025. Studies examining Mediterranean Diet or related anti-inflammatory dietary patterns in relation to preeclampsia prevention were included. We extracted data on study design, population characteristics, intervention details, and outcomes related to preeclampsia or hypertensive disorders of pregnancy.ResultsOur analysis included 12 studies (5 observational studies, 7 randomized controlled trials) with diverse geographical representation. Observational studies demonstrated significant protective associations between higher Mediterranean diet adherence and reduced preeclampsia risk, with effect sizes ranging from 22 to 69% risk reduction. Among the RCTs, two reported statistically significant reductions in hypertension/preeclampsia, while four showed protective trends that did not reach statistical significance. Notable dietary components included extra virgin olive oil and nuts, with variable intervention timing across studies.DiscussionThe findings suggest that Mediterranean diet adherence may reduce preeclampsia risk through multiple complementary pathways: reducing inflammatory markers, alleviating oxidative stress, enhancing endothelial function, balancing angiogenic factors, and improving metabolic parameters. Despite methodological limitations, the Mediterranean diet represents a promising non-pharmacological approach to preeclampsia prevention. Future research should address methodological heterogeneity, expand studies to diverse populations, and elucidate optimal timing and specific components of dietary interventions.